1942
DOI: 10.1128/jb.43.5.573-583.1942
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antibacterial Factors of Human Saliva

Abstract: In previous studies it was found that the growth of 110 of 169 strains of bacteria tested was prevented by human saliva (Bibby, Clough and Hine, 1938). This effect was more marked against some types of organisms than against others, those most affected being bacilli and cocci isolated from air and water; those least affected, organisms isolated from the mouth. Differences occurred in the inhibitory potency of saliva from individual to individual and from time to time. Dissimilarities were noted between the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1949
1949
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It should be recognized that the general approach adopted here, i.e., that of using a bacterium as an absorbent of a salivary antibacterial substance, was explored almost 40 years ago (25). Among other studies, the investigators reported that incubation of M. lysodeikticus with saliva in the cold for 24 h resulted in the removal of an anti-staphylococcal factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be recognized that the general approach adopted here, i.e., that of using a bacterium as an absorbent of a salivary antibacterial substance, was explored almost 40 years ago (25). Among other studies, the investigators reported that incubation of M. lysodeikticus with saliva in the cold for 24 h resulted in the removal of an anti-staphylococcal factor.…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of saliva that contribute to its role in the maintenance of oral health include buffers, mucins and glycoproteins (hydration and lubrication of epithelial surfaces), and antibacterial factors (3,15,16,18). The antibacterial properties of saliva have long been recognized (10,25) but had received relatively little attention until knowledge of the composition of the oral flora associated with states of health and disease (caries, periodontal diseases, mucosal infections) accumulated (3,16).…”
mentioning
confidence: 99%
“…For many years it has been reeognized that there are substances presetit in saliva which can inhibit the growth of lactobacilli (Hill 1939, Kesteren et al 1942, Kerr & Wedderburn 1958, Green 1959, Zeldow 1959. This antilactobacillus substatice has been shown by Dogon & Amdur (1970) to be cotiiposed of two thiocyanate-dependent systems.…”
Section: Atiti-lactobacillits Systetnmentioning
confidence: 99%
“…Interactions between the members of a complex indigenous microbiota could be critical determinants of the delicate biochemical balance between the cohabiting microorganisms and the tissues of their host, the status of which determines the relative states of health and disease (Dubos, 1954). The existence of such complex, but little understood, interrelationships in the oral cavity is evident (Bibby et al, 1938;Van Kesteren et al, 1942;Bj6rnesjo, 1950;Thompson and Johnson, 1951). Although numerous antagonisms between members of the oral microbiota have been described, as manifested by inhibition of growth (reviewed by Rosebury et al, 1954), few instances have been reported of the inhibition of a specific biochemical activity of one microorganism by other microorganisms.…”
mentioning
confidence: 99%